Influence of employee capability and relational process on service quality and customer outcomes in customer relationship management - Ramli, Suriana (2017)
Customer Relationship Management (CRM) has been the main concept in establishing, maintaining and enhancing a meaningful long term relationship between firms and customers. Competent employees, effective processes and technology support are crucial to achieve this objective. Accordingly, the aim of this paper is to examine the influence of the employee relational capability, relational information processes and CRM technology employed by the firms on the perception of services quality. And subsequently examine the relationship of services quality on customer satisfaction and loyalty. Using a quantitative research approach, the survey questionnaires were distributed to 448 bank customers in Klang Valley area. Partial Least Square (PLS) software was applied to examine the hypotheses. The results revealed that there are significant influences between employee relational capability and relational information processes on services quality. It further confirms the influence of services delivery quality to customer satisfaction and loyalty. Although, there is no direct relationship between relational information processes and services delivery quality, there is partial mediation between relational information processes and services delivery quality which is mediated by CRM technology. CRM technology is also found to partially mediate the relationship between employee services capability and services delivery quality. The results will be useful for CRM managers in developing proper strategy to enhance CRM services delivery performance by empowering employee with the right skills and competencies; aligning the processes and adopting effective CRM technology. Academicians could further explore the areas of employee intelligence in identifying the right competencies mix relevant to business.This study has successfully filled the gap in literature by empirically establishing the influence of employee relational capability on services delivery outcomes. And the affirmation of the role of technology as mediator on services quality.